Role of the renal sympathetic nervous system in mediating renal ischaemic injury-induced reductions in renal haemodynamic and excretory functions - Salman, I.M.; Ameer, O.Z.; Sattar, M.A.; Abdullah, N.A.; Yam, M.F.; Najim, H.S..; Khan, A.H.; Johns, E.J. (2010)
Methods: Anaesthetised male Sprague-Dawley rats were subjected to unilateral renal ischaemia by clamping the left renal artery for 30 min followed by reperfusion. Following acute renal denervation clearance experiments were performed. In a different set of experiments, the renal nerves were electrically stimulated at increasing frequencies and responses in renal blood flow and renal vascular resistance were recorded. Results: Denervated post-ischaemic acute renal failure (ARF) rats showed higher urine flow rate, absolute and fractional sodium excretions, urinary sodium to urinary potassium, glomerular filtration rate and basal renal blood flow but lower basal renal vascular resistance (all p < 0.05 vs innervated ARF rats). Potassium excretion was significantly lower in denervated group as per fractional (p < 0.05 vs innervated ARF rats) but not absolute potassium excretion (p > 0.05 vs innervated ARF rats). The rise in mean arterial pressure and renal vasoconstrictor response to renal nerve stimulation were blunted in denervated ischaemic ARF rats (all p < 0.05 vs innervated ARF rats). Renal histopathology in denervated ARF rats manifested a significantly lower medullary congestion, inflammation and tubular injury compared to innervated counterparts (p < 0.05 vs innervated ARF rats). Conclusions: The findings strongly suggest the involvement of renal sympathetic tone in the post-ischaemic events of ischaemic ARF, as the removal of its action to a degree ameliorated the post-ischaemic renal dysfunctions.